Sedentary behavior patterns in non-pregnant and pregnant women - Marquis Hawkins; Youngdeok Kim; Kelley Pettee Gabriel; Bonny Jane Rockette-Wagner; Lisa Chasan-Taber (Preventive Medicine Reports, 2017)
Sedentary behavior has been associated with adverse health outcomes among pregnant women; however, few studies have characterized sedentary behavior patterns in this population. We described patterns of accelerometer-determined indicators of sedentary behavior among a national sample of US pregnant (n = 234) women and non-pregnant (n = 1146) women participating in the NHANES 2003-06 cycles. We included women with ≥4 days of accelerometer wear of ≥10 h/day. A count threshold of <100 cpm was used to describe sedentary behavior as: 1) total accumulated sedentary time by bout length categories; 2) accumulated sedentary time within discrete bout length categories; 3) mean, median, and usual bout length; and 4) and bout frequency. Both non-pregnant and pregnant women spent up to 60% of their accelerometer wear time in sedentary behavior depending on the minimum bout threshold applied. Sedentary time was higher among pregnant women compared to non-pregnant women when lower bout thresholds (i.e. 10 min or less) were applied. The majority of total sedentary time was accumulated in bouts lasting <10 min. The women averaged less than two prolonged sedentary bouts (i.e., ≥30 min) per day, which accounted for nearly 20% of total accumulated sedentary time. When applying a minimum threshold of at least 15 min, sedentary time increased across pregnancy trimesters, while sedentary time was similar across trimesters when using lower thresholds. These findings provide the first characterization of accelerometer-determined indicators of sedentary behavior in pregnant women. The minimum bout threshold applied influenced estimates of sedentary time and patterns sedentary time accumulation across pregnancy trimesters.